Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae) - Sudasinghe, Hiranya; Meegaskumbura, Madhava (Zootaxa, 2016)
Ompok argestes, a new species of silurid catfish, is described from the southwestern lowlands of Sri Lanka. The new species is distinguished from all other species of Ompok in the Indian subcontinent by a combination of the following characters: body color pattern mottled; predorsal profile uniformly convex; maxillary barbels reach or extend slightly beyond base of dorsal fin; eye diameter 14.2–17.1% head length (HL); body depth at anus 19.8–22.3% standard length (SL); head width 14.3–16.8% SL; caudal peduncle depth 5.6–6.5% SL. Callichrous ceylonensis Günther is shown to be a valid species that is apparently restricted to Sri Lanka, distinguished by a combination of the following characters: distinct concavity in predorsal profile; origin of pelvic fin beneath or slightly posterior to the origin of the dorsal fin; maxillary barbels 108–166 % HL; mandibular barbels 16.1–33.7 % HL; and 58–66 anal-fin rays.